Microlasers based on GaAs and Si. (December 2019) - Zhukov, A E; Maximov, M V; Kryzhanovskaya, N V
Abstract: Results are presented on microlasers with quantum dot active region grown on either GaAs or Si substrates. The optical resonator of these lasers represents a microdisk supporting whispering-gallery modes with a Q-factor in excess of 30'000. When operating in continuous-wave mode without temperature stabilization, the microlasers have the threshold currents of mA-range with the minimal threshold current density of 250 A/cm 2 . Under direct small-signal modulation, the -3dB modulation bandwidths were measured to be above 6 GHz with a little effect of self-heating on the performance. The consumed electric power was estimated to be about 2 pJ/bit. The achieved performance is a significant breakthrough in realization of low-threshold high-speed temperatrure-stable operation of microlasers compared with the previously reported parameters for the devices of comparable sizes.